Workflow modeling using UML, Declarative Tools and WEB2.0 - Gamito, R. (2010)
Manual translation of UML diagrams to programmatic code is tedious and error prone. Many CASE tools allow computer code to be generated from Class Diagrams, but fewer, if any, allow the transformation of Activity Dia- grams (ADs) in executable and workflow defining computer code. Our project aims at: • Translating UML ADs into the ISCO programming language; • Building a workflow execution system that runs the translations; • Building a graphical tool to create and edit workflows, and visualize the executions. Defending that UML ADs can specify executable workflows, we present an ISCO based workflow engine, acting over the information extracted from Activity Diagrams and integrated into a platform that allows a user to graph- ically model and manage workflows within a web environment. The server, built with ISCO, assures the data persistence and the execution of the work- flows. Communication with the server is performed through AJAJ.